Toward Equity and Diversity in Literacy Research, Policy, and Practice: A Critical, Global Approach. (September 2017) - Morrell, Ernest
Can growing inequities between rich and poor and massive manifestations of hatred and intolerance amid rising tides of global populism inspire a focus on equity and diversity in literacy research, policy, and practice? Can such calls for change be collaborative rather than competitive? Can we envision self-love, wellness, and intercultural understanding as compelling ends of a reimagined literacy pedagogy? Toward these ends, this essay offers demographic, moral, and economic imperatives for fundamentally reconsidering literacy policy and practice. It then presents five "big" ideas. We must ask different questions, we must identify and problematize our notions of success, we must advocate for the equitable distribution of material resources, we must fight for bottom-up accountability practices, and we must envision new literacy practices that reflect our new global reality. Finally it advocates a global postcolonial critical literacies framework where teachers are positioned as intellectuals and agents of change, where students have opportunities to collaboratively produce and distribute multimodal compositions, where children have access to a wider array of literary texts that enable them to become powerful, reflexive readers of the word and the world, and where parents and communities are partners in the project of nurturing powerful readers, authors, and speaker.